2009
DOI: 10.1007/s10103-009-0673-4
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for the treatment of buccal candidiasis in rats

Abstract: The study objective was to evaluate the effects of photodynamic therapy on buccal candidiasis in rats. After experimental candidiasis had been induced on the tongue dorsum, 72 rats were distributed into four groups according to treatment: treated with laser and methylene blue photosensitizer (L+P+); treated only with laser (L+P-); treated only with photosensitizer (L--P+); not treated with laser or photosensitizer (L-P-). The rats were killed immediately, 1 day, or 5 days after treatment, for microscopic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 21 publications
5
74
0
10
Order By: Relevance
“…This finding is in agreement with that demonstrated by Kömerik et al, 15 who also verified no damage to periodontal tissues of rats submitted to PDT. Junqueira et al 53 described fewer epithelial alterations and lower chronic inflammatory response in rats submitted to PDT and more intense lesions in rats treated only with laser. In the present study, yeast and pseudohyphae were observed only in the keratinized layer without invasion of the epithelium and the inflammation in the subjacent connective tissue was scored as mild for all mice infected with C. albicans, whether or not they were submitted to PDT.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with that demonstrated by Kömerik et al, 15 who also verified no damage to periodontal tissues of rats submitted to PDT. Junqueira et al 53 described fewer epithelial alterations and lower chronic inflammatory response in rats submitted to PDT and more intense lesions in rats treated only with laser. In the present study, yeast and pseudohyphae were observed only in the keratinized layer without invasion of the epithelium and the inflammation in the subjacent connective tissue was scored as mild for all mice infected with C. albicans, whether or not they were submitted to PDT.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts to investigate the possibilities of clinical application of PDI against local candidiasis have been undertaken (23,24). Photodynamic therapy was proposed for the treatment of buccal candidiasis in rats (9,25). In antifungal photodynamic chemotherapy, three main groups of photosensitizers are used, namely, phenothiazine dyes (e.g., (e.g., hematoporphyrin derivative [HpD] and Photogem), and phthalocyanines (e.g., Pc4 and RPL068) (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…PDT is a therapeutic strategy that involves the combination of a nontoxic photosensitizer (PS) and a harmless visible light source [19]. The excited PS reacts with molecular oxygen to produce highly reactive oxygen species, which induce injury and death of microorganisms [20].…”
Section: Introductionmentioning
confidence: 99%